Further data on interrogative suggestibility and compliance scores following instructed malingering - Hansen, Ingo (Legal and criminological psychology, 2010)
Purpose. This study examined whether people can successfully feign high levels of interrogative suggestibility and compliance as measured by the Gudjonsson Suggestibility Scales (GSS) and the Gudjonsson Compliance Scale (GCS) when given instructions to malinger. Methods. Participants (N = 90) were randomly allocated to one of three groups that received: (1) instructions to give into leading questions in order to look vulnerable to suggestions, (2) instructions to be compliant with the examiner, or (3) the standard GSS/GCS instructions. Results. One of the two malingering instructions led to modestly elevated scores of total suggestibility, while subscales remained unaffected. In contrast, both malingering groups obtained highly elevated compliance scores. Conclusions. These findings suggest that heightened suggestibility is rather difficult to malinger, thereby confirming the reliability of the GSS. On the other hand, it might be easier to malingering compliance as measured with the self-report GCS.